A retrospective analysis of inpatient cardiac arrests over one year at a tertiary heart attack and cardiothoracic centre identifying potential candidates for an inpatient extracorporeal cardiopulmonary resuscitation service. (May 2020) - Harrogate, Suzanne; Stretch, Benjamin; Seatter, Rosie; Finney, Simon; Singer, Ben
Introduction: Extracorporeal cardiopulmonary resuscitation (ECPR) is an internationally recognised treatment for refractory cardiac arrest, with evidence of improved outcomes in selected patient groups from cohort studies and case series. In order to establish the clinical need for an in-hospital extracorporeal cardiopulmonary resuscitation service at a tertiary cardiac centre, we analysed the inpatient cardiac arrest database for the previous 12 months. Methods: Evidence-based inclusion criteria were used to retrospectively identify the number of patients potentially eligible for extracorporeal cardiopulmonary resuscitation over a 12-month period. Results: A total of 261 inpatient cardiac arrests were analysed with 21 potential extracorporeal cardiopulmonary resuscitation candidates meeting the inclusion criteria (1.75 patients per month, or 8% of inpatient cardiac arrests (21/261)). The majority (71%) of these cardiac arrests occurred outside of normal working hours. Survival-to-discharge within this sub-group with conventional cardiopulmonary resuscitation was 19% (4/21). Conclusion: Sufficient numbers of refractory inpatient cardiac arrests occur to justify an extracorporeal cardiopulmonary resuscitation service, but a 24-h on-site extracorporeal membrane oxygenation team presents a significant financial and logistical challenge.